Quorum sensing em cianobactérias - Daniel Albuquerque Pereira (2014)
The terminology quorum sensing is used to identify a cellular communication phenomenon in the bacterial domain, which happens when a bacteria population reaches a defined cellular density. During the activation of the phenomenon changes in the expression of several genes and consequently in the physiology of the cell are triggered. Concerning cyanobacteria, there is a lack of information about quorum sensing. Some studies show that quorum sensing inducer compounds may alter physiological characteristics of certain cyanobacteria strains. Besides that, indirect evidences have shown that cellular density may influence microcystin production. The capacity to form blooms in certain conditions is also an important characteristic found in the cyanobacteria group. In these conditions the cellular density of a population may reach elevated numbers, consisting of an ideal scenario for quorum sensing. There are a remarkably number of studies regarding cyanobacterial blooms, but little is known about what happens with a population at molecular and physiological levels. The aim of this study was to characterize four strains of cyanobacteria regarding the production of peptides and to use these strains in experiments with the objective of investigating evidences of quorum sensing system in cyanobacteria and its connection with the synthesis of oligopeptides. In order to fulfill these objectives biochemical and molecular techniques were used. The results obtained showed that the production of oligopeptides is affected by cellular density, being, in most cases, higher in situations with an elevated number of cells. It was demonstrated by real time PCR that acylhomoserine lactone autoinducers (AHLs), which are responsible for the activation of the quorum sensing in various groups of gram-negative bacteria, affect the transcription of genes linked to the production of microcystins, cyanopeptolins and microviridins. Through ELISA assays it was also seen that AHLs affect the microcystin production in the same pattern in which they affect the transcription of genes connected to its synthesis. With this work it was observed that cellular density and possibly quorum sensing are key factors in secondary metabolite synthesis in cyanobacteria and should be considered when studying these compounds and their connection with the environment.